Evaluating Creative Therapy Effectiveness on Children with Special Needs through Robust Clustering Techniques - Yotenka, Rahmadi; Yovita, Zulma (Enthusiastic : International Journal of Applied Statistics and Data Science, 2024)
The study examined the progress of Children with Special Needs (CWSN) in the Center for Students with Special Needs (Pusat Layanan Peserta Didik Berkebutuhan Khusus, PLPDBK) Semarang through creative therapy methods. Based on the primary data collected from the observation of 56 children over eight sessions of therapy. The study employed the Robust Clustering Using Links (ROCK) clustering algorithm to evaluate children’s social interaction and behavior development, fine motor skills, and cognitive capabilities. The clustering process revealed four distinct types of CWSN that, for the most part, were between the ages of 6 and 10 years old. The study found that although the stability of these development features was often seen, there was a possibility for improvements in certain categories. The study highlighted the potential of targeted interventions and modern treatments that regularly elevate children to “5” or the “very good” developmental category during the vital age range of 6 to 10 years. These findings call for greater inclusion in educational policy and therapies that can be designed to accommodate the various needs of children.